An Analysis to Students’ Speaking Anxiety and Emotional Well-Being in English Language Teaching: English - Ni Wayan Giri; Yohanes Gatot Sutapa Yuliana; Regina (Prodi Tadris Bahasa Inggris, 2023)
English Foreign Language aspect, speaking anxiety is a major concern for students. According to the previous study, it gives negatively impact their whole educational experience. Furthermore, past study has paid little attention to the effect of speaking anxiety on students' emotional well-being by examining the relationship between speaking anxiety and emotional well-being. This library research seeks to better understand the connection between students' speaking anxiety and emotional well-being. The study makes use of a thorough analysis of the literature that has already been published on the subject, including studies looking at the emotional effects of speaking anxiety, its prevalence and causes, as well as how it affects language learning. Considering these results, the study provides a thorough understanding of the complex connection between speaking anxiety and emotional well-being in the context of ELT and looks into additional factors that might affect speaking anxiety from some aspect, such as language proficiency, the classroom setting, and cultural background. Research on students' speaking anxiety and emotional well-being has found that anxiety can have a negative impact on language learning. Students frequently worry about how others see them, which causes them to communicate less effectively. The study discovered that speaking anxiety, exam anxiety, and fear of bad grades were the primary causes of speaking anxiety in English-language classrooms. In conclusion, this library research intends to offer helpful insights into the difficulties faced by language learners in terms of speaking anxiety and its effects on emotional wellbeing to educators to support encourage positive language learning experiences and advance the well-being of students.